The Role of Semantic Context in Early Morphological Processing - Whiting, Caroline M.; Cowley, Richard G.; Bozic, Mirjana (Frontiers in Psychology, 2017)
There is extensive evidence pointing to an early, automatic segmentation of written words into their constituent units (farm-er, wit-ness); however, less is known about the potential role of contextual information in modulating this analysis. We adapted the standard masked priming paradigm to include an overt semantic prime in order to examine whether semantic context influences morpho-orthographic segmentation of complex words. In particular, we asked how the context will affect processing of semantically opaque forms (witness), where the embedded stem (wit) is incompatible with the meaning of the whole form. Results showed no masked priming facilitation for opaque forms in the presence of a semantic prime, indicating that context can influence early morphological analysis. Priming was found for both semantically transparent and opaque forms (farmer-farm, witness-wit) when there was no semantically-related context, consistent with the literature and an account positing early blind segmentation. These findings provide an important update to the long-standing debate on early morphological processing in written word recognition.